Construção e interpretação de diagramas de extremos e quartis por alunos portugueses do 9.º ano de escolaridade - Carvalho, Maria José (2019)
This study deals with the difficulties of 9th grade Portuguese students in the building and interpreting of boxplots (DEQ). The study is based on the responses given by 93 9th grade students to 2 questions on the DEQ in a written diagnostic test. By examining the configurations of the objects and mathematical processes that intervene in the students' resolutions, we have identified discrepancies between the personal meanings reached by the students and the institutional meanings intended in the construction and interpretation of the DEQ, noting that: (i) in the construction of the DEQ we observed confusions in the form of presenting a DEQ by incorporating its numeric support in the diagram itself, and difficulties in the accuracy to be considered for the support scale of the support when the data's variation domain is greater; and (ii) in the interpretation of DEQ, there are clear difficulties in analyzing the distributional form of the data through a DEQ, observing the tendency for the student to respond based on the intuitive perception of the symmetry and dispersion of the distribution, without resorting to statistical measures in their justifications. We also observed that the construction of the DEQ is easier than its interpretation. These results corroborate the idea that the analysis of aggregate data, using DEQ, is not an easy task to understand by students of this level of education, so we suggest a greater articulation between DEQ construction activities and interpretation activities.